Relationship of Outpatient Satisfaction With Services Provided by The Officer in General Clinic of Public Health Services Center Kajhu Aceh Besar - Fahrisal Akbar; Susanti Susanti (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
The existence of community health centers at the moment is still not in line with expectations and desires of the majority of society. Many people who are not satisfied with the services provided by the health workers, it can be seen from many of the patients who still complain. In addition, the attitude of health workers who offend even hurt the feelings of the patient, so that will further lower the level of confidence in the health service. The purpose of this study was to determine the relationship of outpatient satisfaction with services provided by the officer in general clinic of Public Health Services Center Kajhu Aceh Besar.This research is descriptive analytic with quantitative approach and cross-sectional design. The population in this study were all outpatients who visited in the general clinic of public health services Kajhu Aceh Besar, at least, 4 visits totaling 1508 patients. The sample in this study amounted to 98 people and sampling techniques performed by accidental sampling. This study was conducted on February 1 to 29 in 2008, held at the Public Health Services Center Kajhu Aceh Besar. Data collected by interview using a questionnaire to the respondents.The results of this study were obtained, there is no relationship between the variables availability of health facilities with outpatient satisfaction (p-value = 0.179; df = 1; alpha = 0.05). The relationship between the variables of achievement of health care, patient perception, acceptance of health care with outpatient satisfaction (p-value = 0.000; df = 1; alpha = 0.05). From the results of this research, it is recommended that public health officers can improve public health services in the future. In addition, it is expected that the government to immediately establish a public health services center that is located not far from residential areas, so it can be easily affordable for people who need medical care quickly.Keywords: Public Health, Satisfaction, Patient, Health Services